Rethinking restraint in psychiatric services: A Kantian ethical and legal analysis - Cemile Hurrem Ayhan; Suat Akkoyun; Kadriye Aslan; Bihter Türkmenoğlu Polat (Nursing Ethics, 2026)
The use of restraint in psychiatric care remains one of the most ethically contested practices in mental health services, reflecting an enduring tension between the duty to ensure safety and the obligation to respect patient autonomy. Although coercive interventions are often justified as necessary responses to risk, their ethical legitimacy remains uncertain, particularly when examined through deontological frameworks. This theoretical paper provides a philosophical and legal analysis of restraint practices, drawing on the ethical theory of Immanuel Kant to critically evaluate the moral boundaries of coercion. Focusing on the Turkish context, the paper examines how reliance on Article 432 of the Turkish Civil Code, together with the absence of a comprehensive mental health law, shapes the use and justification of coercive interventions. The analysis suggests that current practices are largely grounded in risk-based and paternalistic models that may conflict with the Kantian imperative to treat individuals as ends in themselves. From this perspective, the routine use of restraint risks instrumentalizing patients, thereby undermining their dignity and moral agency. Integrating ethical theory, legal critique, and clinical considerations, the paper argues that restraint can only be justified under highly restrictive conditions, including strict necessity, proportionality, and use as a last resort; however, existing legal and clinical frameworks do not consistently meet these standards. The paper advances a rights-based alternative grounded in supported decision-making and psychiatric advance directives as mechanisms for preserving autonomy. By offering an interdisciplinary and normative framework that links philosophical principles with clinical practice and policy, this study contributes to nursing ethics and highlights the central role of nurses in transforming coercive care practices.